ECONOMIC EFFECTS OF CHEMICAL FRUIT THINNING OF THE YOUNG TREES - Milić, Biserka; Keserović, Zoran; Magazin, Nenad (Economics of Agriculture, 2011)
Control of apple trees productivity, during the first years of bearing is essential for maintaining high and regular yields in the entire exploitation period. Removing redundant fruitlets has to be done every year, either by hand or using chemical thinning compounds. The object of this research was to optimize the intensity of chemical fruit thinning according to yield and income in Golden Delicious apple orchard, in the second and third fruiting season. Three rates of 6- benzyladenine (BA) were applied to thin fruits: 100, 150 and 200 mg/l. Calculated income decreased after BA application by 12,5-21,5% compared to the untreated group. The most efficient treatment was 200 mg/l BA, regarding average fruit weight, diameter and yield which nearly reached the planned yields. Additional correction of fruit number per tree by hand thinning was the least necessary after treatment with 200 mg/l BA.